1997
DOI: 10.1143/jjap.36.2229
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Transmission Loss of Chalcogenide Glass Fibers

Abstract: The temperature dependence of transmission loss for IR-transmitting chalcogenide glass fibers of sulfur (S)-based, selenium (Se)-based and tellurium (Te)-containing glasses were investigated above room temperature. The influence of temperature on transmission loss significantly depended upon the kind of chalcogen element in the glass. The losses of S-based and Se-based glass fibers were slightly sensitive to temperature. On the other hand, the loss of Te-containing glass fibers increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Considerable efforts by several Japanese corporations and agencies laid the groundwork for future developments in ChG fibers, including the Nippon Telegraph and Telephone Public Corporation (NTT) [157,323,324], Hitachi, Ltd. [325][326][327][328][329], Horiba, Ltd. [330], Non-oxide Glass R&D Co., Ltd. [331], the Kyota Semiconductor Corporation [332], the HOYA Corporation [333], Uniquely, ChGs cover the broadest IR spectrum of all IR glasses, have the highest optical linear and nonlinear refractive indices, and offer the widest tuning range of optical parameters achieved through compositional engineering. ChG fibers may potentially cover the entire span of QCL wavelengths.…”
Section: Chalcogenide Glass Infrared Fibersmentioning
confidence: 99%
“…Considerable efforts by several Japanese corporations and agencies laid the groundwork for future developments in ChG fibers, including the Nippon Telegraph and Telephone Public Corporation (NTT) [157,323,324], Hitachi, Ltd. [325][326][327][328][329], Horiba, Ltd. [330], Non-oxide Glass R&D Co., Ltd. [331], the Kyota Semiconductor Corporation [332], the HOYA Corporation [333], Uniquely, ChGs cover the broadest IR spectrum of all IR glasses, have the highest optical linear and nonlinear refractive indices, and offer the widest tuning range of optical parameters achieved through compositional engineering. ChG fibers may potentially cover the entire span of QCL wavelengths.…”
Section: Chalcogenide Glass Infrared Fibersmentioning
confidence: 99%
“…5 indicates that sulfide and selenide glass fibers may be inadequate for many far-infrared applications. In this case, glasses containing tellurium are required to achieve wide IR transparency [23,[29][30][31][32][33][34]. One of the main challenges for the fabrication of long wave infrared fibers is to obtain a glass with a high tellurium content which does not crystallize during the fiber drawing process [34] and does not exhibit high charge carrier losses [23].…”
Section: Tailoring the Optical Window Of Chalcogenide Glass Fibersmentioning
confidence: 99%
“…The mechanism of multiphonon absorption for the telluride fiber is the same as that of the sulfide fiber discussed above. Inagawa et al 16 have shown that for the Ge-As-Se-Te glass system the activation energies for the multiphonon and free-carrier absorption are 0.06 eV ͑23-67°C͒ and 0.01 eV ͑77-127°C͒, respectively. Figure 8 shows that for the telluride fiber at T Յ 60°C the increase in loss beyond 9 m is mainly due to multiphonon absorption.…”
Section: ϫ4mentioning
confidence: 99%
“…For the sulfide and the telluride fibers, d͑␣ RS ͒͞dT is determined and listed in Table 3 16 T g ϭ 473 K ͑sulfide͒, 538 K ͑tellu-ride͒, and dn͞dT ϭ 1 ϫ 10 Ϫ5 K Ϫ1 ͑sulfide͒, 9 ϫ 10 Ϫ5 K Ϫ1 ͑telluride͒. 16 At T ϭ 70°C for a 5-m-long sulfide fiber between 1 and 5 m the change in loss due to Rayleigh scattering, d␣ RS , is calculated to be less than 3.0 ϫ 10 Ϫ8 dB. Similarly at T ϭ 60°C for a 5-m-long telluride fiber, between 5 and 9 m, d␣ RS is calculated to be less than 2 ϫ 10 Ϫ9 dB.…”
Section: ϫ4mentioning
confidence: 99%